2009
DOI: 10.1007/s12257-009-0167-z
|View full text |Cite
|
Sign up to set email alerts
|

Removal and inactivation of viruses during the manufacture of a high-purity antihemophilic factor IX from human plasma

Abstract: The purpose of this study was to evaluate the efficacy and mechanisms of the solvent/detergent (S/D) treatment, DEAE-toyopearl 650M anion-exchange column chromatography, heparin-sepharose 6FF affinity column chromatography, and Viresolve NFP filtration steps employed in the manufacture of high-purity antihemophilic factor IX (GreenNine VF) from human plasma, with regard to removal and/or inactivation of blood-borne viruses. A variety of experimental model viruses for human pathogenic viruses, including human i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 35 publications
(29 reference statements)
0
8
0
Order By: Relevance
“…The acetylated resin bound none of the PPV in solution, as shown in Figure 3. The amino control resin, which has amine groups on the surface and is a weak ion exchange resin, was used because ion exchange resins may have inherent virus removal properties (24, 25); this allowed for comparison of peptide ligands to an anion exchange resin. The amino resin removed more virus from solution in the later column volumes than in the earlier column volumes (Figure 3).…”
Section: Resultsmentioning
confidence: 99%
“…The acetylated resin bound none of the PPV in solution, as shown in Figure 3. The amino control resin, which has amine groups on the surface and is a weak ion exchange resin, was used because ion exchange resins may have inherent virus removal properties (24, 25); this allowed for comparison of peptide ligands to an anion exchange resin. The amino resin removed more virus from solution in the later column volumes than in the earlier column volumes (Figure 3).…”
Section: Resultsmentioning
confidence: 99%
“…This is not surprising, as anion exchange columns are often tested for their ability to clear viruses (35). It has been shown that a Q‐Sepharose column was able to clear 3 log of PPV when loaded at pH 6.5 (36) and as high as 5 log of MVM when loaded in Tris buffer at pH 8.0 (14). This follows the trend that increasingly basic solutions will make the virus surface more negatively charged, which would cause increasingly stronger binding of the virus to an anion exchange column.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, it's well known that any chromatography purification step leads to the reduction of virus contamination not less than 0.5-3.0 log 10 per step [17,21]. This phenomenon can be explained by the fact that the chromatographic adsorbent, while firmly retaining the target protein, allowed washing out unrelated or weakly bound viruses, demonstrating a "filtering" model.…”
Section: Introductionmentioning
confidence: 99%